Herbicides and plant physiology - Cobb, Andrew (Wiley-Blackwell, 2010)
Herbicides continue to make a spectacular contribution to modernsafe crop production. It is essential to understand how thesecompounds work in plants and their surroundings to properlyfacilitate the development of more effective and saferagrochemicals. This book provides that information in a succinctand user-friendly way.The second edition of this very well-received and highly thoughtof book has been fully up-dated with much new information ofrelevance to the subject, particularly in the areas of cell andmolecular biology.